Transcriptome profiling identifies genes/pathways associated with experimental resistance to paromomycin in Leishmania donovani. Issue 3 (December 2017) - Verma, Aditya; Bhandari, Vasundhra; Deep, Deepak Kumar; Sundar, Shyam; Dujardin, Jean Claude; Singh, Ruchi; Salotra, Poonam
Abstract: Widespread resistance towards antimony and reports of relapses following miltefosine treatment has severely affected the management of visceral leishmaniasis (VL) in the Indian subcontinent. Paromomycin (PMM), an aminoglycoside antibiotic, has been licensed for VL treatment in India in 2007. Although its use is still restricted in the field, unraveling the molecular mechanism of resistance towards PMM is the key to preserve the drug. In this study, PMM resistant lines were selected up to 100 μM of PMM in three distinct field isolates of Leishmania donovani at promastigote stage. The resistance induced at promastigote level was also evident in amastigotes which showed 6 fold decreases in PMM susceptibility. Comparative transcriptome profiling of PMM resistant (PMM-R) and the corresponding PMM sensitive (PMM-S) parasites revealed modulated expression of 500 genes (1.5 fold cut off) in PMM-R parasites. Selected genes were validated for their modulated expression by quantitative real-time PCR. Functional classification and pathway analysis of modulated genes indicated probable adaptations in drug resistant lines which included a) reduced oxidative phosphorylation; b) increased glycosomal succinate fermentation and substrate level phosphorylation; c) dependency on lipids and amino acids for energy generation; d) reduced DNA synthesis and increased DNA damage repair and e) decreased protein synthesis and degradation. Interestingly, PMM-R parasites showed a marked increase in PMM susceptibility in presence of verapamil and amlodipine, antagonists of Ca 2+ channel that are also modulators of ABC transporters. Moreover, infection of macrophages by PMM-R parasites led to modulated nitric oxide (NO) levels while reactive oxygen species (ROS) level remained unaltered. The present study highlights the putative mechanisms of PMM resistance in Leishmania. Graphical abstract: Image 1